Comparative analysis of navy bean starch nanoparticles prepared via ultrasound, enzymatic debranching, and their synergistic application - Nora Ali Hassan; Aijun Hu; Ammar B. Altemimi; Jie Zheng; Ran Han; Darya Khan; Mohammad Ali Hesarinejad; Tarek Gamal Abedelmaksoud (Scientific Reports)
Abstract Navy bean starch (NS) nanoparticles were prepared using ultrasonication, enzymatic debranching, and their combined application. Ultrasonication was conducted at power levels ranging from 100 to 600 W for durations up to 25 min, while enzymatic debranching was carried out for up to 360 min. In the combined treatment, starch was subjected to ultrasound (300–600 W) in conjunction with enzymatic action for up to 30 min.The samples were selected based on the best particle size, amylose content, and reducing sugar values. The ultrasonicated starch sample (US) was chosen at 600 watts for 3 min, the enzymatically debranched sample (ES) at 15 min, and the combined sample (E-US) at 450 watts for 15 min. The particle sizes of the NS, US, ES, and E-US samples were 7480, 231.08, 230.4, and 25 nm, respectively. Scanning electron microscopy (SEM) showed surface fissures in NS and US samples, grooves in ES, and irregularity in E-US. The swelling index rose in NS and US while debranching improved solubility in ES and E-US. In vitro digestibility indicated good resistant starch in ES and E-US from retrogradation, confirmed by differential scanning calorimetry (DSC) analyses. Fourier-transform infrared analysis (FTIR) showed samples were organized in crystalline structures, and X-ray diffraction (XRD) indicated E-US had the highest crystallinity.Finally, The E-US sample, treated with 450W ultrasound for 15 min, showed the smallest particle size and highest modification efficiency.